Estudo da cinética de oxidação em altas temperaturas da liga SV15 aplicada na fabricação de sedes de válvulas de escape de motores automotivos - Alano, José Henrique (Universidade Federal de São Carlos, 2014)
The SV15 alloy is applied in the production of the exhaust valve seats of automotive engines. The conditions of service in which the part is submitted require materials resistant to oxidation because of high temperature and aggressive atmosphere in which the material is exposed. The evaluation of high-temperature oxidation of the SV15 alloy is important therefore contributing in the selection or not of the material in other applications as severe as the automotive engine. The high-temperature oxidation in the alloy SV15 was studied by thermogravimetry in an atmosphere of O2 for a period of one hour at temperatures of 660°C, 740°C, 860°C and 900°C. The microstructure and chemical composition of the alloy were determined by scanning electron microscopy (SEM), and the phases present in the alloy were studied by X-ray diffraction (XRD). The SEM technique was also used to assess the microstructure, morphology, thickness and chemical composition of the oxide layer. To determine the phases presented by the oxide layer were used the techniques of Fourier transform infrared spectroscopy (FTIR), FT-Raman and XRD. The oxides formed at 660°C and 740°C follow the linear rate law, while the layers formed at 860°C and 900°C showed two stages of oxidation, an initial linear stage and a second parabolic stage. The first stage of oxidation showed an oxide formed mainly by NiCr2O4 while the second stage was composed of Cr2O3. The oxidation mechanism in the first stage of oxidation was controlled by the reaction rate of the oxygen with the metallic substrate, while the second stage of oxidation was controlled by reducing the diffusion of Ni+2 through the NiCr2O4 layer.
Study of high temperature oxidation kinetics of sv15 alloy applied in the manufacture of exhaust valve seat inserts for automotive engines
Keywords: Engenharia de materiais; Cinética de oxidação; Ligas de níquel; Oxidação em altas temperaturas; Camada de óxido; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA